2009
DOI: 10.1007/s00784-009-0282-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey on German dentists regarding the management of craniomandibular disorders

Abstract: The purpose of the present investigation was to identify the most frequent therapies and, in particular, the prescription patterns for occlusal splints for the management of craniomandibular disorders (CMDs) used by German general dentists and specialists. Additionally, the knowledge and opinion of the practising dentists were examined. All active members of the statutory dental insurance providers of the German North Rhine (n = 5,500) and the Westphalia-Lippe area (n = 4,984) were surveyed with a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
6
21
0
5
Order By: Relevance
“…Our response rate (56 %) is a further strength of our study and was comparable to other studies in this area [23], with reported response rates of 7.6 to 9.0 % in studies in South Korea [17] and Germany [14] and 83 to 87 % reported in studies in Sweden and the USA [20,21,25]. A separate nonresponder analyses revealed no substantial differences between respondents and nonrespondents in gender distribution and proportion of practitioners performing TMD diagnostics.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our response rate (56 %) is a further strength of our study and was comparable to other studies in this area [23], with reported response rates of 7.6 to 9.0 % in studies in South Korea [17] and Germany [14] and 83 to 87 % reported in studies in Sweden and the USA [20,21,25]. A separate nonresponder analyses revealed no substantial differences between respondents and nonrespondents in gender distribution and proportion of practitioners performing TMD diagnostics.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, we had expected to find a higher proportion of practitioners making use of behavioral therapy. However, our findings support the results of previous studies reporting low experiences and rare recommendations of those treatment modalities by general dental practitioners [14,19,20]. This lack of utilization of behavioral therapy may be caused by a lack of training in psychosocial competence and understanding in undergraduate curricula.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations